Re-Inventing the Food Supply Chain with IoT: A Data-Driven Solution to Reduce Food Loss - Ranganathan, Vaishnavi; Kumar, Peeyush; Kaur, Upinder; Li, Sarah; Chakraborty, Tusher; Chandra, Ranveer (IEEE Internet of Things Magazine, 2022)
The global food supply chain needs to evolve to meet a 50 percent increase in food demand by 2050. While food production grows every year, according to a report by the Food and Agriculture Organization (FAO), around 25 percent of roots and tubers, 20 percent of fruits and vegetables, 8 percent of grains and pulses, and 13 percent of animal products are lost before distribution. The majority of such losses are attributed to inadequate monitoring and poor handling during storage and transport. Moreover, the handling of produce in the supply chain also impacts its nutritional content and shelf life. Such losses, when coupled with the rising frequency of epidemics and climate events, further exacerbate the problem of food security for the global population. In addressing the problem of food loss in the supply chain, the biggest hurdle is the lack of traceability and information. On one hand, precision farming helps improve food production efficiency. On the other hand, useful insights post-harvest are not measured due to cost limitations. The ones that are measured often end up in silos or are lost. To overcome these challenges, we propose a framework that leverages low-power IoT sensing networks, smart edges, and data-driven optimization to re-invent the supply chain. In this work, we derive from lessons learned while working with various agricultural supply chain partners and share insights based on some technology solutions that we have explored. We take a bottom-up approach in analyzing the major challenges faced by today's food supply chain. Starting with individual food pallets, we propose ways to develop an agile and low-cost data pipeline that can sense and track the food as it moves through the global supply chain. Further, we propose a dedicated optimization framework that can leverage cloud analytics to boost sustainability and efficiency in the global food chain to meet the growing demand.